INCONSISTENCY AND AMBIGUITY IN ACHIEVING SUSTAINED COMPETITIVE ADVANTAGE - Agustini, Rr Rooswanti Putri Adi (Airlangga Development Journal, 2025)
The television industry often experiences imitation. A commercial television station in the Indonesian television industry, Trans Media, experienced imitation of its program, technologies, and human resources. In the case of Trans Media, the imitation does not affect its sustained competitive advantage. It is not clear to competitors which resources generate sustained competitive advantage. Ambiguity is at the heart of this difficulty. In this study, we examine how an organization's strategies create ambiguity and achieve sustained competitive advantage in the middle of imitation efforts by competitors. We propose a Z-Model of inconsistency in creating ambiguity and achieving sustained competitive advantage. The academic and managerial implications are further discussed in this study.